A Comparison of Two Methods for Solving Electromagnetic Field Integral Equation - L. Jebli (International Journal of Differential Equations)
The present paper aims to compare Harrington's direct method of moment (MoM) with the conjugate gradient method (CGM) by evaluating the total current solving the electric field integral equation (EFIE). Based on their performances, the number of iterations needed for convergence, storage, and the level of precision, it is found that the direct MoM is more efficient than other iterative CGM.